The SAGE handbook of propaganda - Baines, Paul, 1973-; O'Shaughnessy, Nicholas J., 1954-; Snow, Nancy (London : SAGE Publications Ltd., 2020)
The SAGE Handbook of Propaganda unpacks the ever-present and exciting topic of propaganda to explain how it invades the human psyche, in what ways it does so, and in what contexts. As a beguiling tool of political persuasion in times of war, peace, and uncertainty, propaganda incites people to take, often violent, action, consciously or unconsciously. This pervasive influence is particularly prevalent in world politics and international relations today. In this interdisciplinary Handbook, the editors have gathered together a group of world-class scholars from Europe, America, Asia, and the Middle East, to discuss leadership propaganda, war propaganda, propaganda for peace marketing, propaganda as a psychological tool, terror-enhanced propaganda, and the contemporary topics of internet-mediated propaganda. Unlike previous publications on the subject, this book brings to the forefront current manifestations and processes of propaganda such as Islamist, and Far Right propaganda, from interdisciplinary perspectives. In its four parts, the Handbook offers researchers and academics of propaganda studies, peace and conflict studies, media and communication studies, political science and governance marketing, as well as intelligence and law enforcement communities, a comprehensive overview of the tools and context of the development and evolution of propaganda from the twentieth century to the present: Part One: Concepts, Precepts and Techniques in Propaganda Research; Part Two: Methodological Approaches in Propaganda Research; Part Three: Tools and Techniques in Counter-Propaganda Research; Part Four: Propaganda in Context.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Propaganda -- Handbooks, manuals, etc; Marketing -- Psychological aspects -- Handbooks, manuals, etc